Digital storytelling and memory institutions: A case study using activity theory. Issue 1 (27th December 2016) - Detlor, Brian; Hupfer, Maureen E.; Smith, David Harris
ABSTRACT: This paper describes a case study investigation of a city‐wide digital storytelling initiative led by two libraries and one municipal cultural department in Hamilton, Canada. Data collection involved one‐on‐one interviews, document review, and participant observations with governance stakeholders from the two libraries and municipal cultural department involved in the case study. Using activity theory as a conceptual framework, data were analyzed using grounded theory techniques. A variety of factors – motivations, goals, actions, tools, rules, divisions of labour, tensions and contradictions – were found to influence the implementation of the digital storytelling initiative under investigation. Importantly, activity theory provided a robust, holistic framework for understanding and describing the phenomenon of digital storytelling initiatives led by memory institutions.